Case Report: Purtscher Retinopathy Following Subarachnoid Hemorrhage and Femur Fracture - Huddleston McDaniel, Amy; Senechal, Roxanne (Canadian Journal of Optometry, 2023)
Purtscher retinopathy is a rare microvasculopathy which occurs following trauma. Clinical presentation consists of cotton wool spots, retinal hemorrhages, and Purtscher flecken within the posterior pole. A similar display of findings has been associated with a heterogenous group of systemic disorders, but the classification of Purtscher-like retinopathy is reserved for these non-traumatic etiologies. Although the pathogenesis remains to be fully understood, clinical and experimental evidence implicate an occlusive vasculopathy of the precapillary arterioles. Clinical presentation resolves in the months following trauma; however, visual prognosis is variable. There are presently no evidence-based treatments available for Purtscher retinopathy.